Activity and Stability of Oxides During Oxygen Evolution Reaction‐‐‐From Mechanistic Controversies Toward Relevant Electrocatalytic Descriptors - Zeradjanin, Aleksandar R.; Masa, Justus; Spanos, Ioannis; Schlögl, Robert (Frontiers in Energy Research, 2021)
Plotting the roadmap of future “renewable energy highway” requires drastic technological advancement of devices like electrolyzers and fuel cells. Technological breakthrough is practically impossible without advanced fundamental understanding of interfacial energy conversion processes, including electrocatalytic water splitting. Particularly challenging is the oxygen evolution reaction which imposes high demands on the long-term activity of electrocatalysts and electrode support materials. To cross the “Rubicon” and in a deterministic manner claim that we developed principles of rational catalyst design, we need first to comprehend the determinants of electrocatalytic activity as well as character of their time evolution. How reliable are reported activity and stability trends, could we interrelate activity and stability, and how meaningful that relation really is are some of the important questions that have to be tackled in building of a more comprehensive view on critically important anodic oxygen evolution.